1841 Mich. Pub. Acts 29-30, No. 18, §14. - (:unkn) unknown (General Publisher, 1841)
And the said common council shall have power . . . relative to the keeping and sale of gunpowder in said village[.]
--
Keywords: TRANSFER; MANUFACTURE & STORAGE OF GUNPOWDER